Effect of feeding frequency on the efficiency of nitrogen utilization under low level of protein feeding in growing crossbred bulls - Bhar, R; Katiyar, R C (The Indian Journal of Animal Sciences, 2012)
Efficiency of N-utilization under 4 feeding systems was studied offering daily concentrate allowance once (FS-1), twice (FS-2), mixed with wheat straw (FS-3), and in 8 functions at hourly intervals (FS-4) with wheat straw as basal roughage in growing crossbred bull supplying 25% less crude protein them the recommended level (NRC). Total daily N-intake under 4 feeding systems ranged from 73.6±1.0 to 75.0±0.7 g/head. The digestibility of proximate constituents was not affected by any of the feeding systems. The urinary N·excretion was lowest under FS-4 (20.5±0.5g/ day) and for other systems it ranged from 22.7±1.7 to 25.1±0.7 g/day. The percentage of N-retained out of the total N-absorbed daily was significantly higher (0.05) in FS-4 than FS-3, whereas both these systems were comparable to FS-1 and FS-2 indicating that at the lower level of protein allowance frequency of feeding may have little effect on its utilization efficiency. However, the pattern of rumen ammonia-N concentration definitely showed the possibility of efficient N-utilization under higher frequency of feeding in ruminants.